Fotodynamická terapie s preparátem visudyne v lécbe vlhké formy vekem podmínené makulární degenerace--dvouleté výsledky - Kolár, P; Vizdová, D; Vlková, E (Casopis lekaru ceskych, 2006)
BACKGROUND: Photodynamic therapy with Visudyne represents a new method in treatment of the wet form of age-related macular degeneration. METHODS AND RESULTS: Effectiveness of photodynamic therapy with Visudyne was confirmed at our department in the group of 49 patients (13 men, 36 women) of mean age 72.7 years with predominantly classical and occult choroidal neovascular membrane in subfoveal localization in wet form of age-related macular degeneration. The observation period in all patients in this group was 24 month. During the observation period, 27 patients with predominantly classical choroidal neovascular membrane underwent 1 to 5 treatments (mean 1.8). Before the treatment the average best corrected visual acuity was 0.696 +/- 0.20 logMAR. At the end of observation period the average best corrected visual acuity was 0.985 +/- 0.39 logMAR. Best corrected visual acuity dropped by 2.88 lines of ETDRS (early treatment diabetic retinopathy study) visual charts. 22 patients with the genuine occult choroidal neovascular membrane underwent during the observation period 1 to 3 treatments (mean 1.5). Average best corrected visual acuity before the treatment was 0.755 +/- 0.25 logMAR. At the end of observation period the average best corrected visual acuity was 0.909 +/- 0.42 logMAR. We found out the decrease of average best corrected visual acuity by 1.55 lines of ETDRS charts. CONCLUSIONS: Decrease of the average best corrected visual acuity less than 3 lines at ETDRS charts is considered as stabilisation of the finding. In our group this goal was achieved in 2/3 of patients.
Keywords: Photochemotherapy; senioři; Choroidal Neovascularization; Fluorescein Angiography; Photosensitizing Agents; Male; Female; makulární degenerace; Aged; fotosenzibilizující látky; Macular Degeneration; neovaskularizace choroidey; porfyriny; mužské pohlaví; ženské pohlaví; Porphyrins; fotochemoterapie; Verteporfin; verteporfin; fluoresceinová angiografie; lidé; Humans